The outcome of the patients with lumbar disc radiculopathy treated either with surgical or conservative methods - Kavuncu, V; Kerman, M; Sahin, S; Yilmaz, N; Karan, A; Berker, E (Vsp Bv, 2002)
The aim of the present study was to evaluate the functional outcome and the factors influencing the chronicity and frequency of pain in patients with lumbar disc herniation and radiculopathy. A cohort of 85 patients with low back pain and sciatica due to lumbar disc radiculopathy were followed-up retrospectively. Patients with sciatica due to lumbar disc herniations who were treated surgically (n = 40, age 41.4 +/- 12.7) or conservatively (n = 45, age 43.4 +/- 11.4) were recruited into the study. The average follow-up period was 29.8 months. Surgically treated patients exhibited improved neurological symptoms but higher visual analogue scale (VAS) for pain and disability scores (p < 0.001). A significant correlation was noted between VAS and disability scores (r = 0.86, p < 0.001) whereas there was no significant correlation between these scores and lumbar mobility. The demographic and clinical variables like gender, body-mass index and pain localization do not seem to affect clinical prognosis. In conclusion, the outcomes of the patients with lumbar disc radiculopathy may differ by the type of the treatment. No indicators were found to be related with the long-term prognosis of these patients.
Keywords: lumbar disc radiculopathy; disability; prognosis